Can primary insert be used in revision knee prosthesis? - Omer Bozduman; Yasin Koker; Ilker Polat; Burak Akan (Medicine Science, 2021)
The aim of osteoarthritis treatment is to reduce pain and relieve functional limitations. Total knee replacement is now frequently used in the ultimate treatment of osteoarthritis. High patient satisfaction after total knee prosthesis leads to an increase in primary cases and parallel to this, an increase in the revision rate. In our study, a total of 42 patients (43 knees) who underwent single-stage revision knee replacement surgery between October 2009 and January 2016 and followed-up until November 2020 (4 years minimum, 11 years maximum) were included in the study. 41 of these patients were female and 1 was male. Two revision operations were performed for one patient. The mean age of patients when revision knee prosthesis was performed was 70.3 ± 6.7 (minimum 51; maximum 87). 42 patients; 23 had complaints from the left knee and 20 from the right knee. The mean follow-up time after revision is 56.2 ± 1 months. The postoperative clinical evaluation of the patients was made according to the American knee association score, and the differences between the clinical results of 3 different implants used differently were revealed. The most striking result is that the clinical results of normal inserts used in semi-constrained revision surgery are more successful than semi-constrained inserts. Both the range of motion and satisfaction were found to be higher in the patients. Regarding the insert differences between the prostheses used, we have seen that those using normal inserts increase the knee association score better than those using constrained or hinged inserts, and at the same time, we think that these normal inserts used will last longer than restrictive inserts. [Med-Science 2021; 10(3.000): 881-5]